Sistem Pemberian Pakan Otomatis Untuk Peternakan Ayam Kampung Dengan Internet of Things - Annur, Muhammad; An’nur, Muhammad (Journal Information Technology Trends (JITRENDS), 2024)
Free-range chicken farming in Indonesia has high economic potential, but manual feeding is time-consuming and labor-intensive. This challenge is especially felt by busy farmers, leading to delays in feeding, triggering aggressive behavior, and cannibalism in chickens. The Internet of Things (IoT) technology offers a solution through an automatic feeding system that optimizes the farmer's time and effort. This study aims to design and implement an IoT-based automatic feeding system for free-range chicken farming. This system utilizes temperature and humidity sensors to monitor the coop conditions in real-time and regulate feeding according to a predetermined schedule while also checking feed availability. The research results show that this system can perform feeding based on real-time temperature and humidity monitoring and check feed availability.